Understanding the free trade agreement : Trans-Pacific Partnership : summary of the full text of Trans-Pacific Partnership - Unobagha, Chibueze; Unobagha, Chibueze ([United States] : [publisher not identified], 2015)
This book is a full summary of the 4,500 pages of the text agreement which was agreed on October 5, and officially released for the public use on November 2015.
Keywords: Trans-Pacific Strategic Economic Partnership Agreement. -- (2015 October 5).; Free trade -- Pacific Area; Free trade -- United States; Foreign trade regulation -- Pacific Area; Foreign trade regulation -- United States; Pacific Area -- Commerce -- United States; United States -- Foreign economic relations -- Pacific Area; Pacific Area -- Foreign economic relations -- United States; United States -- Commerce -- Pacific Area